SHAPE AND OBJECT RECOGNITION APPLICATION USING AUGMENTED REALITY BASED FLASHCARD MEDIA - Irma Noviana; Muhammad Fairuzabadi; Puji Handayani Putri (CV. Fahr Publishing, 2024)
Flashcards are small cards that contain pictures or photos and some text below them. Augmented Reality is a technology that overlays graphics from the real world and the virtual world so that it can be viewed realistically and interactively. The development of mobile or Android-based information technology makes it easier to learn shape recognition material and object recognition material, especially for kindergarten children, starting from introducing examples of objects with different shapes around them according to their shape. They will serve as a foundation before moving on to the next level. The problem in this research is that the flashcard media is limited to certain material which is made manually, and not all teachers use information technology as a learning medium, thereby limiting the availability of certain material. The aim of this research is to develop an Augmented Reality-based flashcard learning application using Android devices for kindergarten children. Data collection techniques used include observation, interviews and literature study. Based on the problems above, a solution is needed in the form of an application to support learning activities using Android Augmented Reality that recognizes shapes and objects through direct visualization of 3D objects. The end result is an AR flashcard application for shapes and objects.